Researching the Efficacy of Studio Education and the Profession’s Futurity: The Faculty Project of Architectural Studio Education - Michael Karassowitsch (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
The research is to develop architectural value in the educational studio environment through the superordinate program of architectural practice. The studio environment is proposed as an architectural project for the faculty in which the student architect may experience architectural value. Some architectural schools maintain an atmosphere of architectural value in continuity of a long history and other factors. This paper discusses the research for realizing architectural value in the context of the technological value proxy utilized in the profession and its associations around the world. The studio becomes simultaneous projects for faculty and students. The faculty project engages 2nd-year semester III studio at the Sushant School of Art and Architecture, integrating with students’ projects, as a means for this development. Although it is limited by faculty knowledge and student expectation, we can conclude characteristic effects whereby this approach will lead to directed evolution of the educational environment and influence professional practice.